Hyperchaos in a new four-dimensional autonomous system - Correia M.J.* (2010)
In this letter we report a new four-dimensional autonomous system, constructed from a chaotic Lorenz system by introducing an adequate feedback controller to the third equation. We show that when parameters are conveniently chosen, the control method can drive the chaotic Lorenz system to hyperchaotic regions. Analytical and numerical procedures are conducted to study the dynamical behaviors of the proposed new system. © 2010 World Scientific Publishing Company.